Luxembourg - diversifying a small open economy - Stráský, Jan (OECD Publishing, 2015)
Developing activities in areas other than finance would help to sustain growth and deal with the declining potential output and trend productivity growth that Luxembourg's economy is facing. Given the relatively high labour costs, Luxembourg's future comparative advantages are likely to lie in higher value added and skill intensive activities. Further development of Luxembourg's high living standards thus requires strengthening the economy's growth potential via further diversification of activity in high value added sectors. Stepping up investment in knowledge based capital and enterprise innovation can help Luxembourg to maintain and further develop comparative advantages in high value added activities. The government is promoting the formation of enterprise clusters by providing networking, infrastructure investment and financial support for research and development. To enhance the efficiency of the government's policy, high priority should be given to outcome-oriented evaluation. This is required to ensure that costly infrastructure investment yields good results. Further efforts should be made to create synergies via cross-border initiatives, in particular with respect to research. Experience in other countries points to the importance of regulatory framework conditions in product and labour markets to spur enterprise dynamics. Regulation in professional services can be made more competition friendly, and impediments to labour force participation, notably for women, can be reduced. Productivity and innovation are also affected by the effectiveness of the secondary education system to produce skilled workers, which in Luxembourg is hampered by high repetition rates among students. This Working Paper relates to the 2015 OECD Economic Survey of Luxembourg (www.oecd.org/eco/surveys/economic-survey-luxembourg.htm)
Keywords: Economics